2021
DOI: 10.1093/cid/ciab503
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IFN-γ Secretion in Blood Samples Collected Before and After Treatment of Varying Stages of Lyme Disease

Abstract: Background QuantiFERON ELISA with Borrelia burgdorferi peptide antigens was previously shown to reliably detect IFN-γ in blood samples from adult patients with early Lyme disease and the response disappeared rapidly after treatment. We evaluated the response before and after appropriate antibiotic therapy in adolescent and adult subjects with more diverse stages of the illness. Methods Blood was obtained from clinician-identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For latent tuberculosis, the IGRA is widely accepted as a diagnostic tool (91), and studies have suggested similar techniques to discriminate active from past Q-fever using whole blood IFN-g assays (92,93). Two studies performed in Northern America reported a higher sensitivity for a whole blood IFN-g assay in EM patients compared to serology (37,94). However, we could not reproduce these findings in a European cohort (95), where B. afzelii is the most common cause of EM, in contrast to B. burgdorferi s.s. in Northern America.…”
Section: Discussionmentioning
confidence: 99%
“…For latent tuberculosis, the IGRA is widely accepted as a diagnostic tool (91), and studies have suggested similar techniques to discriminate active from past Q-fever using whole blood IFN-g assays (92,93). Two studies performed in Northern America reported a higher sensitivity for a whole blood IFN-g assay in EM patients compared to serology (37,94). However, we could not reproduce these findings in a European cohort (95), where B. afzelii is the most common cause of EM, in contrast to B. burgdorferi s.s. in Northern America.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study further strengthen the view that there are no serologic markers, which would unambiguously identify patients with ongoing LNB and, thus, in need of antibiotic treatment, although the absence of serum IgG VlsE reactivity to some degree argues against acute LNB. Therefore, novel approaches both in the direct detection of Borrelia, such as detection of cell-free DNA in human plasma [16], and in non-antibody based indirect methods, such as metabolite-profiling [17], or analysis of leucocyte response [18], are needed.…”
Section: Discussionmentioning
confidence: 99%